2009
DOI: 10.4155/fmc.09.80
|View full text |Cite
|
Sign up to set email alerts
|

Thiosemicarbazones: The New Wave in Cancer Treatment

Abstract: The anticancer effects of thiosemicarbazones were once solely attributed to the inhibition of ribonucleotide reductase, an enzyme involved in the rate-limiting step of DNA synthesis. However, the mechanism behind this inhibition was initially not described. The ability of thiosemicarbazones to chelate metal ions has now been recognized as a major factor in their antiproliferative effects. This mini-review discusses current advances of an emerging 'new wave' of thiosemicarbazones as potent anticancer agents, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(107 citation statements)
references
References 42 publications
3
94
0
3
Order By: Relevance
“…Since then, several generations of TSCs have been tested for their chemotherapeutic potential (96,108). In early mechanistic studies, the anticancer activity of TSCs was attributed to their ability to inhibit ribonucleotide reductase, an enzyme involved in DNA synthesis and repair (18).…”
Section: Iron Chelators As Chemotherapeutic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, several generations of TSCs have been tested for their chemotherapeutic potential (96,108). In early mechanistic studies, the anticancer activity of TSCs was attributed to their ability to inhibit ribonucleotide reductase, an enzyme involved in DNA synthesis and repair (18).…”
Section: Iron Chelators As Chemotherapeutic Agentsmentioning
confidence: 99%
“…Among those known to chelate iron and target topoisomerase IIa are dexrazoxane, (E)-N,N-dimethyl-2-(quinolin-2-ylmethylene)hydrazinecarbothioamide (TSC-24), and Dp44mT ( Fig. 3) (18,96,108,209). TSC-24 is considered a catalytic top2a inhibitor due to a direct interaction with the ATPase domain of top2a, which leads to a blockade of ATP hydrolysis.…”
Section: Raomentioning
confidence: 99%
“…Some studies have revealed that triapine shows considerably higher efficacy than N-hydroxyurea in both enzyme and cell assays. Recent studies also show that some thiosemicarbazone derivatives inhibit topoisomerase II a enzyme [9][10][11][12] . However, some naphthalene derivatives have also been reported as potent apoptosis inducers, P-glycoprotein inhibitors, microtubule inhibitors or glutamamide analogs [13][14][15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Desta maneira, a replicação de base é dificultada ou impedida de ocorrer e/ou são criadas lesões nas fitas de DNA por ruptura oxidativa [34]. tiossemicarbazonas, envolvendo a inibição da enzima RR [35]. A estabilização da enzima ocasionada pelo centro de ferro não-heme, é essencial para sua atividade catalítica.…”
Section: Tiossemicarbazonasunclassified
“…E, na presença do PCT, ocorre a inibição da RR devido à coordenação do composto ao centro metálico de ferro [36]. As células cancerígenas expressam níveis elevados de RR em relação às células normais, devido a sua maior taxa de proliferação e, por este motivo, elas se tornam mais susceptíveis para tal coordenação [35].…”
Section: Tiossemicarbazonasunclassified